Hydrocarbon poisoning in children: 1-year retrospective study - Hatti, Sachin S; Uplaonkar, Vinod; Honnalli, Charanraj (Indian Journal of Child Health, 2018)
Context: Accidental hydrocarbon poisoning continues to be a major problem in children in India. Objectives: The objectives of the study were to study the demographics, clinico-laboratory profile of hydrocarbon poisoning in children admitted to our hospital from April 2015 to March 2016. Secondary Objective: The secondary objective of the study was to determine corelation between vomiting and development of pneumonia after hydrocarbon consumption. Materials and Methods: In this retrospective descriptive study, all children with the history of hydrocarbon consumption and admitted to the hospital during the study period were included in the study. The medical records of these children were reviewed retrospectively, data were recorded in a standard pro forma and were analyzed. Chi-square test was used for comparing differences between categorical variables. For interpretation of results, significance was adopted at p